Erosion behavior of nickel diffusion membranes in conditions of water electrolysis - Glazunov, G.P.; Bodnar, A.S.; Konotopskiy, A.L.; Vinogradov, D.M.; Maznichenko, S.M.; Garkusha, I.E. (Problems of Atomic Science and Technology, 2022)
Preliminary studies of the erosion resistance of Ni diffusion membranes under the conditions of water electrolysis in various modes were carried out. Particular attention was paid to the time dependencies of the current, voltage and the electrolyte temperature during the process. Both electrodes, anode and cathode, were in the form of tubes of Ni-99.5% wt. The electrolyte was pure drinking water after the filter with mineralization (ppm) 14, as well as water with the addition of sodium bicarbonate (mineralization 140...160 ppm). It is demonstrated that after several hours of operation cathodes showed no signs of erosion or other damages. The degree of erosion was assessed by weighing, and the state (morphology) of the surface was visually examined using an optical microscope. As for the anode, even when electrolyzing sufficiently pure water (ppm = 14), there is noticeable erosion and surface damage. To elucidate the reasons for such behavior of Ni electrodes, further studies are planned, in particular, using some other materials as an anode. Проведено попередні дослідження ерозійної стійкості дифузійних мембран з Ni в умовах електролізу води в різних режимах. Особливу увагу було приділено вимірюванню залежності струму та напруги на електродах, температури електроліту від часу процесу. Обидва електроди, анод та катод, були виконані у вигляді трубок з Ni-99,5 ваг.%. Як електроліт використовували чисту воду після фільтра з мінералізацією 14 проміле, а також воду з додаванням соди (мінералізація 140...160 проміле). Показано, що катоди після декількох годин роботи не виявили жодних ознак ерозії чи інших ушкоджень. Ступінь ерозії оцінювали шляхом зважування, а стан (морфологію) поверхні візуально за допомогою оптичного мікроскопа. Що стосується анода, навіть при електролізі достатньо чистої води (14 проміле), спостерігається суттєва ерозія та пошкодження поверхні. Для з’ясування причин такої поведінки планується провести подальші дослідження, зокрема, використовуючи інші матеріали в якості аноду.